2018
DOI: 10.3389/fmars.2018.00027
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Trichodesmium spp. and Diatom-Diazotroph Assemblages in the North Pacific Subtropical Gyre

Abstract: In oligotrophic ocean regions such as the North Pacific Subtropical Gyre (NPSG), N 2 fixation (i.e., diazotrophy) by a diverse consortium of microorganisms has been shown to contribute significantly to new production and particle export. In 2015 and 2016, we measured near-monthly abundances of the large cell-sized (> 10 µm) diazotrophic genera Trichodesmium and diatom-associated Richelia and Calothrix spp. in the NPSG via microscopy and quantitative PCR of nifH genes. Of these genera, we find Trichodesmium to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 53 publications
3
67
3
Order By: Relevance
“…Because of variations in nifH gene copy number per cell in different diazotrophs and methodological issues (e.g., nonspecificity of primers and probes used in qPCR), conversion to cell numbers is not straightforward. More details can be found in Text S1 in the supporting information (see also White et al, 2018). available radiation (PAR), mixed layer depth (MLD), averaged PAR in the mixed layer (PAR mld ), chlorophyll-a concentration ([Chl]), and modeled surface iron concentration (Fe).…”
Section: Updating the Global Diazotrophs Databasementioning
confidence: 99%
“…Because of variations in nifH gene copy number per cell in different diazotrophs and methodological issues (e.g., nonspecificity of primers and probes used in qPCR), conversion to cell numbers is not straightforward. More details can be found in Text S1 in the supporting information (see also White et al, 2018). available radiation (PAR), mixed layer depth (MLD), averaged PAR in the mixed layer (PAR mld ), chlorophyll-a concentration ([Chl]), and modeled surface iron concentration (Fe).…”
Section: Updating the Global Diazotrophs Databasementioning
confidence: 99%
“…One trait that is widely variable in nature is filament length. It has been widely accepted that the average filament length is 100 cells (46) but more recent studies have suggested that they are typically much shorter, with a geometric mean of 13.2 ± 2.3 cells per filament, but with a mean range of 1.2 to 685 cells per filament in situ (47). Conditions for in situ sampling are widely variable so we hypothesized that filament length plays a role in maintaining growth in different environments: low light, low CO 2 and low N 2 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the many advantages of using this multi-paradigm framework is that we can simulate emergent behavior of a population. In situ data reports a wide mean range of trichome length from 1.2 to 685 cells (47); we used the model to investigate possible causes because this is a difficult phenotype to investigate experimentally. Our simulations suggest that even though longer filaments suffer from diffusional effects that limit growth, they are better able to handle stress (Figure 6) consistent with literature.…”
Section: Discussionmentioning
confidence: 99%
“…This source water was pre‐filtered through 200 μm Nitex mesh in order to exclude grazers. This mesh also excludes large colonies of nitrogen fixers, but, at least for Trichodesmium , this effect is expected to be small (∼ 6% of the total; White et al ). Water was then fed through a plankton net with 20 μm mesh net and cod‐end.…”
Section: Methodsmentioning
confidence: 99%